2010
DOI: 10.1111/j.1747-4949.2010.00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Protocol and Pilot Data for Establishing the Australian Stroke Clinical Registry

Abstract: Australian Stroke Clinical Registry has been well established, but further refinements and broad roll-out are required before realising its potential of improving patient care through clinician feedback and allowance of local, national, and international comparative data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
123
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 128 publications
(124 citation statements)
references
References 21 publications
1
123
0
Order By: Relevance
“…Information includes patient characteristics, quality indicators, and health outcome measures. 9,10 Longer-term patient outcomes are obtained centrally by AuSCR staff using survey methods (eg, for HRQoL) or annual data linkage to national death registrations.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Information includes patient characteristics, quality indicators, and health outcome measures. 9,10 Longer-term patient outcomes are obtained centrally by AuSCR staff using survey methods (eg, for HRQoL) or annual data linkage to national death registrations.…”
Section: Methodsmentioning
confidence: 99%
“…To reduce sampling biases, AuSCR obtains patient data using an opt-out procedure or there is a waiver of consent for patients who die while in hospital. 9 Each year for 2010 to 2014, between 2% and 6% of registrants opted out.…”
Section: Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Australian Stroke Clinical Registry (AuSCR) is a collaborative national effort established in 2009 to routinely record processes of care and health outcomes of patients hospitalised with stroke or transient ischaemic attack (see protocol [13] and www.auscr.com.au) with the overall aim of improving real-time adherence to acute stroke evidence-based care indicators in Australia. To date, registry data from Australia have not been examined to compare the characteristics and outcomes of younger adult stroke survivors to older stroke survivors.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, key components of evidence-based acute stroke treatment include the use of intravenous thrombolysis for ischaemic stroke, treatment in a dedicated stroke unit, discharge prescription of an antihypertensive agent and provision of a care plan on discharge [13]. However, researchers in other developed countries have shown that there is differential provision of evidence-based care to younger patients with stroke compared to those who are older with, for example, discharge on antihypertensive medication significantly lower in younger cohorts [14-16].…”
Section: Introductionmentioning
confidence: 99%